2015
DOI: 10.1021/jf505254y
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Residue Monitoring Results for Pork, Chicken, and Beef Samples in Vietnam in 2012–2013

Abstract: A monitoring plan of residual antibiotics in food of animal origin was conducted in Vietnam from 2012 to 2013. Meat samples were collected from slaughterhouses and retail stores in Ho Chi Minh City and Nha Trang. A total of 28 antibiotics were analyzed using a LC-MS/MS screening method. Sulfonamides, fluoroquinolones, and tilmicosin were detected in some of the samples. Sulfaclozine and fluoroquinolones were mainly detected in chicken samples, and sulfamethazine was mainly detected in pork samples. High levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
47
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(53 citation statements)
references
References 27 publications
4
47
1
1
Order By: Relevance
“…The use of large volumes of antibiotics in food-producing animals has been proposed as a contributing factor (Vieira et al, 2011). In this regard, we confirmed residual antibiotics in a significant number of meat samples in a different study (Yamaguchi et al, 2015).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The use of large volumes of antibiotics in food-producing animals has been proposed as a contributing factor (Vieira et al, 2011). In this regard, we confirmed residual antibiotics in a significant number of meat samples in a different study (Yamaguchi et al, 2015).…”
Section: Discussionsupporting
confidence: 79%
“…Moreover, recent reports from Vietnam showed that antimicrobials are extensively used in large-scale pig and poultry farming (CarriqueMas et al, 2015;Dang et al, 2013). In fact, residual antibiotics in a significant number of food samples were observed in Vietnam (Yamaguchi et al, 2015). These circumstances may contribute to the high rates of MDR ESBL-producing bacteria in food in Vietnam.…”
Section: Discussionmentioning
confidence: 99%
“…Sulphonamides, fluoroquinolones, and tilmicosin were detected. Sulfaclozine and fluoroquinolones were mainly detected in chicken samples, whereas sulfamethazine was mainly detected in pork samples [25]. Another study from Vietnam investigating fluoroquinolone and tetracycline residues in 104 fish/shrimp retail samples concluded that overall 27% of retail samples tested positive for either of the two, using a range of techniques [17].…”
Section: Resultsmentioning
confidence: 99%
“…25 In order to reduce the potential exposure risks, more strict maximal residue limits (MRL) of antibiotics in seafood need to be set for Chinese residents. While consumption of seafood alone is unlikely to represent a major human health risk in China, humans are exposed to antibiotics by a variety of other exposure pathways, such as other food intakes, 58,59 drug abuse, 60 tap water, 61 and inhalation of contaminated dust. 62 Moreover, this study did not investigate levels of antibiotic metabolites in the food web from Laizhou Bay.…”
Section: Resultsmentioning
confidence: 99%